Structure of the full-length Shaker potassium channel Kv1.2 by normal-mode-based X-ray crystallographic refinement - Chen, Xiaorui; Wang, Qinghua; Ni, Fengyun; Ma, Jianpeng; Lipscomb, William N. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Voltage-dependent potassium channels (Kv) are homotetramers composed of four voltage sensors and one pore domain. Because of high-level structural flexibility, the first mammalian Kv structure, Kv1.2 at 2.9 Å, has about 37% molecular mass of the transmembrane portion not resolved. In this study, by applying a novel normalmode-based X-ray crystallographic refinement method to the original diffraction data and structural model, we established the structure of full-length Kv1.2 in its native form. This structure offers mechanistic insights into voltage sensing. Particularly, it shows a hydrophobic layer of about 10 Å at the midpoint of the membrane bilayer, which is likely the molecular basis for the observed "focused electric field" of Kv1.2 between the internal and external solutions. This work also demonstrated the potential of the refinement method in bringing up large chunks of missing densities, thus beneficial to structural refinement of many difficult systems.